Staying physically active during the COVID-19 pandemic: Assessing the roles of motivation, basic psychological needs, goal orientation and anticipatory sport persistence - Loerbroks, Lotta; Kersten, Louisa Joyce; Freund, Philipp Alexander (Frontiers in Psychology, 2023)
Nationwide barriers to public and private sport institutions were implemented during COVID-19 lockdowns. Autonomous motivation, perceived fulfillment of basic psychological needs (competence, autonomy, relatedness) and goal orientation coincide with higher persistence rates in physical activity. The aim of this study is to investigate which factors are related to anticipatory sport persistence, a specific form of sport persistence. We conducted an online survey with N = 208 (74% female) participants. Correlation analyses showed that higher anticipatory sport persistence coincides with autonomous motivation (r = .314, p < .01), basic psychological needs (competence r = .528, autonomy r = .446, relatedness at r = .315; all p < .01), and goal orientation (intrinsic r = 450, extrinsic r = .146; all p < .01). Furthermore, multiple regression analysis showed that anticipatory sport persistence can be predicted through intrinsic goal orientation (B = .465. p < .01) and the need for competence (B = .418. p < .01). The importance of anticipatory sport persistence when expecting external barriers to physical activity, the relationship toward sport persistence and possible implications for the planning and perseverance of physical activity plans are being discussed.